Associations between changes in serum uric acid and the risk of myocardial infarction. (1st September 2020) - Tian, Xue; Zuo, Yingting; Chen, Shuohua; Wang, Anxin; Li, Haibin; He, Yan; Zhang, Licheng; An, Ji; Wu, Shouling; Luo, Yanxia
Abstract: Background: The role of serum uric acid (SUA) in development of myocardial infarction (MI) is controversial. The current study aimed to investigate the association between both baseline SUA and changes in SUA and the risk of MI. Methods: The current study included 71, 449 Chinese participants (mean age, 50.9 years) free of MI during the time of follow-up. Participants were divided into 4 categories according to the SUA levels between baseline and the second follow-up: stable low, elevated, reduced and stable high. Multivariate Cox proportion models were used to calculated hazard ratios (HRs) and their 95% confidence intervals (CIs) for MI. Results: During a median follow-up of 8.96 years, 837 MI cases were identified. After adjustment for potential confounders, MI risk was only associated with stable high SUA, the HR was 1.42 (95%CI: 1.02–1.92, p = 0.03), compared with those with stable low SUA. However, there was no association between hyperuricemia at baseline and MI, the HR was 1.14 (95%CI: 0.91–1.42, p = 0.19) compared with those with normal SUA. Subgroup analyses stratified by age, sex, hypertension, diabetes and estimated glomerular filtration rate were also confirmed no significant difference (p-interaction >0.05 for all). Furthermore, mediation analyses revealed 14.14% of association was mediated by hypertension. Conclusions: Only stable high SUA was associated with increased higher risk of MI. Changes in SUA levels in any other direction or high SUA levels at baseline were not associated with risk of MI. Graphical abstract: Unlabelled Image Highlights: Only stable high SUA was associated with the risk of MI. Hypertension served as a mediator in the association of changes in SUA and MI risk. Changes in SUA had better predicting value of MI than baseline SUA.